Modelling the Functional System of Small Business Development in the Republic of Kazakhstan - ABELDANOVA, Aigerim; SMAILOVA, Zhanara; TASPENOVA, Gaukhar; UASHOV, Gilash; AUBAKIROVA, Zhanna; KOZLOVA, Natalya (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The main tendencies of development of small business in the Republic of Kazakhstan are considered in the article. The analysis of crediting of subjects of small business in Kazakhstan is carried out. Recommendations are offered for overcoming the difficulties hampering the dynamic development of small and medium-sized businesses. The solution of these tasks is related to the need to develop small business. At the same time, entrepreneurship (business), like any kind of activity, must have theoretical foundations explaining its essence.